2020
DOI: 10.1177/0033688220945418
|View full text |Cite
|
Sign up to set email alerts
|

Language Learner Engagement During Speaking Tasks: A Longitudinal Study

Abstract: Learner engagement is crucial for ensuring the quality of learning experiences, and yet the study of ‘task engagement’ has received relatively little empirical attention in the language education domain. This article reports on a study exploring the factors contributing to learners’ engagement and disengagement during task performance in an English as a foreign language classroom. Thirty-seven learners performed 10 different speaking tasks implemented over a 10-week period in a Japanese university task-support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 31 publications
3
57
0
2
Order By: Relevance
“…The authors pointed out that such changes can be influenced by many factors, including the perceived value of peer assistance and students' beliefs about collaborative tasks and experiences. Aubrey et al (2020) explored the factors contributing to students' engagement and disengagement during task performance in a language classroom. The results of 10 different speaking tasks over a 10-week period revealed that various factors, at learner-level (e.g., perceptions about language skills), lesson-level (e.g., preparation for the lesson), task-level (e.g., task design), and post-task-level (e.g., evaluation of performance), influenced the students' (dis-)engagement in task.…”
Section: Temporal Aspect Of Student Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors pointed out that such changes can be influenced by many factors, including the perceived value of peer assistance and students' beliefs about collaborative tasks and experiences. Aubrey et al (2020) explored the factors contributing to students' engagement and disengagement during task performance in a language classroom. The results of 10 different speaking tasks over a 10-week period revealed that various factors, at learner-level (e.g., perceptions about language skills), lesson-level (e.g., preparation for the lesson), task-level (e.g., task design), and post-task-level (e.g., evaluation of performance), influenced the students' (dis-)engagement in task.…”
Section: Temporal Aspect Of Student Engagementmentioning
confidence: 99%
“…As another feature, this study incorporates a temporal aspect into its research design to determine how students' task engagement changes (or not) over time. The few studies that have addressed related issues (e.g., Aubrey et al, 2020;Chen & Yu, 2019;Yashima et al, 2016) have examined peer interaction within different tasks and different lessons. However, little research has been carried out about how the students interact with their partners within the same task and how they change (or do not change) their task engagement within a single lesson.…”
Section: Introductionmentioning
confidence: 99%
“…EFL researchers have conducted numerous studies and focused on various aspects of the classrooms and teaching contexts to find out the factors that improve the quality of students' educational paths (Reyes et al, 2012;Ryan and Deci, 2017;Dao et al, 2019;Aubrey et al, 2020). Studies have shown that the general policies of any educational system, the perceived social expectation of teacher-student interactions, and teacher-student biological experiences all affect the dimensions of the teacherstudent relationship in EFL contexts (Jang et al, 2010).…”
Section: Teacher Relatedness and Engagementmentioning
confidence: 99%
“…Google Docs are working documents to which all students in the class have simultaneous access. Items in the scale testing Engagement were formulated based on Aubrey et al (2020), Dörnyei (2019) and Lopez (2011. The scale included statements such as: "The online learning environment provided me with opportunity to engage with my peers", or "[…] to engage with my teacher", which the respondents rated on a 5-point Likert scale ranging from 1 -I completely disagree, to 5 -I completely agree.…”
Section: Methodsmentioning
confidence: 99%